Molecular cloning and expression of TLR in the Eisenia andrei earthworm - Škanta, František; Roubalová, Radka; Dvořák, Jiří; Procházková, Petra; Bilej, Martin (Developmental and comparative immunology, 2013)
Toll-like receptors (TLRs) play an important role in defense responses to pathogens in invertebrates. Here we characterize the first TLR isolated from an oligochaete annelid, namely, Eisenia andrei (EaTLR) and show its expression pattern. The full-length EaTLR cDNA consists of 2615 bp encoding a putative protein of 675 amino acids. The predicted amino acid sequence comprises of an extracellular domain containing 31 amino acid signal peptide and seven leucine-rich repeats (LRR), capped with cysteine-rich N- and C-terminal LRRs followed by a transmembrane domain and cytoplasmic Toll/IL-1R domain (TIR). TIR domains of twenty individual earthworms were sequenced and the variability suggesting the presence of a high number of TLR genes in the genome of E. andrei was observed. Phylogenetic analysis revealed the highest similarity of EaTLR with polychaete annelid, Capitella teleta and TLRs of mollusks and echinoderms. Finally, the highest constitutive expression of EaTLR was observed in the digestive tract. Gene expression was significantly increased in coelomocytes of E. andrei after the challenge with Gram-positive bacteria.
Keywords: Oligochaeta; exprese genu; Gene Expression; sekvence nukleotidů; leucine-rich repeat TIR, Toll/IL-1R domain; EaTLR; fylogeneze; Cloning, Molecular; Phylogeny; Eisenia andrei; klonování DNA; pattern recognition receptor; Eisenia andrei Toll-like receptor; molekulární sekvence - údaje; Amino Acid Sequence; pathogen-associated molecular patterns; PAMPs; toll-like receptory; sekvenční seřazení; Innate immunity; TLR; Toll-Like Receptors; Toll-like receptor; Animals; LRR; zvířata; sekvence aminokyselin; Invertebrates; Molecular Sequence Data; Base Sequence; PRR; Sequence Alignment